Evaluation of Technological Determinism of Mobile Journalism: Case Study of Television Journalists in Indonesia - Firmansyah, Firmansyah; Rangga, Aryana Catur; Kurnia, Septiawan Santana; Othman, Siti Suriani; Fadhli, Ahmad (Komunikator, 2024)
The evolution of smartphone technology has instigated significant shifts in journalistic culture. Both consciously and subconsciously, a multitude of television journalists have embraced mobile journalism (MoJo), especially for correspondents or journalists in the regions. This study aims to elucidate the impact of technological determinism on television journalists and how it fosters a distinctive MoJo work culture. Using a case study methodology, the research integrates observations and interviews with 35 television journalists who have engaged in mobile journalism. Data analysis focuses on four primary areas: technological determinism within journalists in the realms of reductionism, monism, neutralization, and technological imperatives. The research findings suggest that the adoption of MoJo does not obliterate the existing journalistic culture but serves as an alternative avenue for generating diverse and creative news content. The use of technology is inherently tied to the user, highlighting the need for enhanced moral considerations in its application. While the ease of technology facilitates reporting, journalists continue to uphold the content of their reports and maintain their professionalism. The evaluation of the MoJo concept in Indonesia should be supported by product regulations and standardization to ensure it does not become conflated with content creator practices.